2015
DOI: 10.1136/ebmed-2014-110160
|View full text |Cite
|
Sign up to set email alerts
|

Special tests for assessing meniscal tears within the knee: a systematic review and meta-analysis

Abstract: Background Musculoskeletal knee pain is a large and costly problem, and meniscal tears make up a large proportion of diagnoses. 'Special tests' to diagnose torn menisci are often used in the physical examination of the knee joint. A large number of publications within the literature have investigated the diagnostic accuracy of these tests, yet despite the wealth of research their diagnostic accuracy remains unclear. Aim To synthesise the most current literature on the diagnostic accuracy of special tests for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 73 publications
0
35
1
6
Order By: Relevance
“…Joint line tenderness is used as a clinical sign of meniscal pathology , an established risk factor for knee OA . It is included as one of the physical examinations for evaluating tibiofemoral OA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Joint line tenderness is used as a clinical sign of meniscal pathology , an established risk factor for knee OA . It is included as one of the physical examinations for evaluating tibiofemoral OA .…”
Section: Discussionmentioning
confidence: 99%
“…However, at present the significance of these tests in predicting long‐term outcomes of the knee joint is unknown. For the tibiofemoral compartments, joint line tenderness is commonly used in clinical practice to diagnose meniscal pathology , with a sensitivity of 83% and a specificity of 83% , and meniscal pathology is known to predate the onset and progression of knee OA . One study found no association between joint line tenderness and rapid progression to knee arthroplasty within 3 years in individuals with or at risk for knee OA .…”
Section: Introductionmentioning
confidence: 99%
“…One systematic review39 with 4 studies40–43 and 11 additional studies44–54 were included (online supplementary table 6). These 15 studies included 2474 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, no standard criteria exist for referring primary care patients who are experiencing intraarticular knee pain to specialists. [5][6][7] Consequently, orthopedic surgeons are largely responsible for determining whether patients have operable vs manageable knee pain, reducing the time they have available for surgery.…”
Section: Introductionmentioning
confidence: 99%